Hubungan Pengetahuan tentang Penggunaan OAD pada Pasien Diabetes Mellitus Tipe 2 terhadap Kepatuhan Penggunaan Obat Antidiabetes Oral di Puskesmas Singosari Malang - Niken Faramida Sari; Ika Ratna Hidayati; Rizka Novia Atmadani (Jurnal Kesehatan Islam : Islamic Health Journal, 2021)
Abstract. Background: Diabetes Mellitus is a chronic disease characterized by high blood sugar levels in the body and can be caused by the pancreas not being able to produce enough insulin or because the cells in the body cannot respond to the insulin that has been produced. Management includes diet, physical activity, and administration of insulin injections and oral antidiabetic drugs (OAD). The objective of this study is to determine the relationship between knowledge of Type 2 Diabetes Mellitus patients and adherence to oral antidiabetic drug use at Singosari Public Health Center, Malang Regency. Research Methods: This research is analytic observational with a cross-sectional approach. Conducted in July 2021 at the Singosari Public Health Center, Malang Regency, by distributing questionnaires to 66 Type 2 Diabetes patients who met the inclusion criteria. The analysis was carried out with the SPSS application using descriptive and analytic methods. The results of the validity and reliability tests have met the requirements Result and Discussion:. Patients who have good knowledge of 74.2%, 18.2% good knowledge, and 7.6% poor knowledge. Patients with good knowledge were found to have 73% adherence to the use of OAD. Based on the results of the correlation test with Chi-Square, obtained a significant value of p = 0.000. Conclusion iit can be stated that there is a relationship between the knowledge of type 2 DM patients and adherence to the use of OAD at the Singosari Public Health Center, Malang Regency.